Use of native species of "dry forest" for recovering the landscape in the process of closing the dump of the district "Las Lomas" - Piura - Montoro Negrón, Bárbara Elizabeth (2012)
The investigation concerns landscape fragmentation district of Las Lomas in Piura, affected by the existence of an open dump. The study focuses on the possible restoration of the landscape during the decommissioning process. To which we studied the native plant species of dry forest piurano selecting the most resistant and helpful in the recovery process, the same that were placed scenically on the final cover. This process called phytoremediation help the roots of trees and shrubs stabilize the closed area, degrade and absorb waste leachate. Proper placement and subsequent vegetation growth recover the landscape will help the return of displaced wildlife and allow this process to accelerate regenerator for the welfare of the surrounding population.